Predicting the potential suitable habitats of Rosa roxburghii and its key pest Grapholita molesta in China using the MaxEnt Model - Hongling Qin; Shuangshuang Wu; Guoqing Luo; Meifang Lu; Heng Xiang; Zhengbin Li (PLoS ONE, 2026)
Climate change can reshape the potential distributions of crops and their pests, as well as their spatial overlap, with important implications for agricultural security and pest management. Rosa. roxburghii , a key specialty crop in southwestern China, is threatened by its primary pest, Grapholita molesta . Here, we used occurrence records and WorldClim bioclimatic variables to model the potential distributions of both species under current (1970–2000) and future (SSP2–4.5 and SSP5–8.5, 2061–2080) climates via a parameter-optimized MaxEnt model, and analyzed spatial overlap across suitability levels. Model performance was assessed with ENMeval and the continuous Boyce index. Results show that the minimum temperature of the coldest month (bio6) is the main climatic constraint for both species, with R. roxburghii influenced by multiple factors and G. molesta primarily limited by winter low-temperature thresholds. Currently, R. roxburghii ’s suitable areas are smaller and mainly concentrated in southwestern and central China, whereas G. molesta has a much broader potential distribution across China. Although the overall co-occurrence area spans most of the suitable range of R. roxburghii , the majority of this overlap occurs in low-suitability zones, indicating a generally low probability of co-occurrence across much of the distribution. The overlap of highly suitable areas (HSA) between the two species is extremely limited, covering only ~28,800 km² (~0.3% of China’s land area), suggesting that potential high-risk areas are spatially restricted rather than widespread. Under future scenarios, R. roxburghii ’s highly suitable areas are projected to contract and fragment, whereas G. molesta ’s range expands northward. However, the overlap of moderate and highly suitable areas between the two species does not increase and even declines, suggesting that future pest risk is likely to become spatially restructured, concentrating in specific regions rather than intensifying across the entire distribution range. These findings elucidate differences in climatic niche and climate sensitivity between crop and pest, providing a scientific basis for targeted pest management and optimized R. roxburghii cultivation.